Communication and Delivery of Project Activities: A Case Study of Selected Organisations in Kabale Municipality - Aine, Onan (Kabale University, 2023)
The study was about communication and delivery of project activities: a case study of selected organizations in Kabale Municipality. It considered a few Non-Governmental organizations that operate in Kabale district such as Kick Corruption out of Uganda (KICK-U), Kigezi Women in Development (KWID), and Forum for Women in Development (FOWODE). The study was guided by research objectives which were to examine the communication channels used in Non- Governmental Organizations in Kabale district, to find out how Communication affect delivery of project activities in Non-Governmental Organizations of Kabale district and to propose ways in which Communication can be improved for effective delivery of project activities in Non- Governmental Organizations in Kabale district. The study used a descriptive survey design with qualitative and quantitative approaches. The study used a sample size 0f 90 respondents and both interviews and questionnaires were used to collect data from respondents. The study findings indicated that there is minimal communication between project stakeholders and project employees and there is minimal interaction between project donors and beneficiaries and this may have contributed to low delivery of project activities in this organization over years. The study findings indicated findings on communication channels used by Non-Governmental Organizations as emails, websites, television such as TV west in Western Uganda, letters, telephone, meetings, Newspapers, financial reports, brochures, posters, notice board and memos, The study findings indicated findings on effect of communication on delivery of project activities in Non- Governmental Organizations are physical barriers, system design, staff shortage, negative attitude among the staff in an organization, psychological factors, individual linguistic ability, lack of sensitivity, lack of skills, lack of knowledge, duties overload, emotional interference and organizational culture. The study findings indicated findings on ways in which communication can be improved for effective delivery of project activities in Non-Governmental organizations can be improved indicate that availability. use of multiple channels, regular reports, assumptions, body languages, team work, feedback, establishing relevancy, open door policy, getting message across and handling communication problems . Finally the study recommended that the study found out that there are several communication channels in which communication can pass through from the sender to the receiver therefore such channels should be maintained and improved for smooth communication process. The study findings indicate that there are several factors that hinder communication therefore stakeholders should fight hard to handle these factors so that there is smooth communication process.